Metabolite regulation of heat shock protein levels. - Lanks, K W (1983)
When murine L929 cells are briefly exposed to elevated temperature (43 degrees C) they preferentially synthesize heat shock proteins (HSPs) of Mrs 85,000 and 69,000. By the criteria of two-dimensional polyacrylamide gel electrophoresis and partial proteolytic peptide mapping, the Mr 85,000 HSP is indistinguishable from the major cytoplasmic protein whose synthesis and intracellular level were shown previously to be suppressed by glucose deprivation. The mechanism regulating the Mr 85,000 HSP levels is quite sensitive, operating in the range of 0-50 microM glucose. In glucose-free medium, synthesis is at first suppressed but returns to a high level after 3 days as levels of the protein decrease. Synthesis and level of the Mr 69,000 HSP also were affected by glucose deprivation, but this protein appeared to be a complex of several isoelectric and Mr species, so the effects were not as dramatic. Chase experiments show that the half-lives of both the Mr 85,000 and Mr 69,000 HSPs are reduced by a factor of 2.0-2.5 after 5 days of glucose deprivation. The half-life of the Mr 69,000 HSP also was reduced by glutamine deprivation, whereas that of the Mr 85,000 HSP was essentially unaffected. This increase in turnover appears to be sufficient to account for the reduced intracellular level, thus suggesting that glucose sustains high HSP levels mainly by decreasing degradation of the proteins. Although the function of the HSPs is not known, these data support the concept that they have important roles in the general cellular economy and do not function merely as "stress" proteins.